Tingkat Pemahaman Inflasi Mata Uang di Kalangan Gen-Z Studi Kasus di Kecamatan Gondanglegi Malang (International Forum of Researchers and Lecturers, 2025)
Inflation is a condition in which the economy is marked by a general and continuous increase in the prices of goods and services over a certain period. Inflation reflects a decrease in the purchasing power of money due to the rising prices of goods and services. This study aims to analyze the level of understanding of inflation among Generation Z in Gondanglegi District, Malang Regency. Inflation is a crucial economic indicator that affects purchasing power and decision-making, particularly for the younger generation growing up in a dynamic economic landscape.The research uses a qualitative approach with data collected through Google Forms and strengthened with interview data. Respondents were 50 individuals aged between 19 and 25 years, all of whom had graduated from high school (SMA). The data were analyzed descriptively to understand the depth of knowledge and perception of inflation among these individuals.The results indicate that while most respondents are familiar with the term